PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVB SDN 4 PEKANBARU - Viona Resti Resti; Erlisnawati '; Damanhuri Daud Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this research is the low students achievement on social studies IVB grade students of SDN 4 Pekanbaru with average 68,47 and clasical completeness 42,86% within Minimum Criteria Completeness (KKM) stipulated by schools is 75. The study is in the form of classroom action research (PTK) which aims to improve students achievement on social studies IVB SDN 4 Pekanbaru with the application of the approach Contextual Teaching and Learning (CTL). After applied the approach Contextual Teaching and Learning (CTL) increased student learning outcomes in UAS I with an average 70.71 with a large increase from basic score 3.27% with classical completeness amounted to 66.67% (not completed) the average UAS II was 81.90 with a large increase from basic score of 19.61% with classical completeness 85.72% (completed). The average percentage of the activity of teachers in the first cycle of the first meeting is 56.25% with sufficient category and then increased by 12.5% ​​in the second meeting be 68.75% with the good category. At the second cycle of the first meeting the average percentage of the activity of teachers increased by 6.25% to 75% with the good category and at the second meeting increased by 12.5% ​​to 87.5% with very good category. Besides the activity of students in the first cycle the first meeting with the average percentage was 56.25% with sufficient category increased by 6.25% in the second meeting to 62.5% with the good category. At the second cycle of the first meeting the average percentage of the activity of students increased by 12.5% ​​to 75% with the good category and at the second meeting increased by 12.5% ​​to 87.5% with very good category. Based on these results it can be concluded that the application of the approach of Contextual Teaching and Learning (CTL) can improve learning outcomes social studies IVB grade students of SDN 4 Pekanbaru. Key words: Contextual Teaching and Learning (CTL), Students Achievement the Result Of Social Studies